Predictions of Muscle Forces During the Cross-Body Adduction and Hand-Behind-the-Back Tests to Assess Osteoarthritis of the Acromioclavicular Joint - Kamal Gautam; Mohamed Samir Hefzy; Kyle Behrens; Abdul A. Mustapha (Applied Sciences)
Acromioclavicular joint osteoarthritis is prevalent in middle-aged and older people, causing shoulder pain and functional limitations. Despite its prevalence, there are inconsistencies in the physical diagnosis procedures practiced in clinical tests. A recent study introduced a novel hand-behind-the-back (HBB) test, a promising alternative to the traditional cross-body adduction (CBA) test. However, further study was suggested to validate the results obtained. So, this study predicted muscle forces for the cross-body adduction and hand-behind-the-back tests using OpenSim and the AnyBody Modeling System™. This work redefined the joint kinematics for the tests and performed an inverse dynamics analysis to solve the muscle redundancy problem using the generic upper extremity dynamic models available in OpenSim and AnyBody Modeling System™. The results revealed some agreements and significant discrepancies in most muscle force predictions between the OpenSim and AnyBody Modeling SystemTM. Thus, this study underscores the necessity of integrating multiple modeling approaches and comprehensive validation, including experimental data, to enhance the accuracy and reliability of muscle force predictions in shoulder biomechanics during CBA and HBB tests.